The Terminologia Histologica after 10years: Inconsistencies, mistakes, and new proposals - Varga, Ivan; Blankova, Alzbeta; Konarik, Marek; Baca, Vaclav; Dvorakova, Vlasta; Musil, Vladimir (Annals of anatomy, 2018)
This article details our experience with the Terminologia Histologica (TH) and its utility in the teaching of histology, cytology, and clinical medicine (e.g., pathology and hematology). Latin histological nomenclature has been used for 43years, and the latest version of the TH has been in use for 15years (although it was only issued publicly within the past 10years). The following findings and ensuing proposals allow us to discuss key points pertaining to the TH and make important suggestions for potential changes to the TH (such as the exclusion and inclusion of various terms). We classify these changes into six groups: 1.) mistakes in the TH, 2.) discrepancies among various Terminologiae, 3.) discrepancies within the TH, 4.) the repetition of terms, 5.) synonyms in the TH, and 6.) missing terms in the TH. Surprisingly, unlike the anatomical nomenclature, the histological nomenclature has been neglected in the literature. This article addresses this problem by reviewing and summarizing the state of this field, pointing out key discrepancies, offering solutions, and highlighting topics for further discussion.
Keywords: Histology; jazyk (prostředek komunikace); terminologie jako téma; Terminology as Topic; Language; Histological terminology; Terminologia Histologica; Terminology; dějiny 20. století; Nomenclature; dějiny 17. století; History, 20th Century; dějiny 21. století; anatomie; History, 17th Century; Histological nomenclature; History, 21st Century; Anatomy